Increased classical monocyte subsets in South Asians compared to White Caucasians at risk for coronary atherosclerosis. (14th October 2021) - Hosseini, F; Franco, C; Selvakumar, K; Whalen, B; Kaila, K; Sellers, S; Malhi, N; Shahriari, M; Lee, S; Farkouh, M; Verma, S; Taylor, C; et al.
Abstract: Background: South Asians (SA) have an increased prevalence of coronary artery disease (CAD) and myocardial infarction compared with age- and sex-adjusted White Caucasians (WC). The mechanism for this increased risk is poorly understood. While classical CD14++CD16- monocytes act as independent predictors of cardiovascular disease, differences in the distribution of monocyte subsets between SA and WC have not been established. Purpose: We aimed to determine if differences exist in monocyte subsets between SA and WC at risk for CAD. Methods: Our cohort consisted of 119 consecutively enrolled patients (59 SA, 60 WC) at intermediate or higher risk for CAD by the INTERHEART score using self-reported history and physical exam. A single blood sample was collected prospectively for the purpose of monocyte analysis. Flow cytometry using dual colour fluorescence (CD14, CD16) within the monocyte gate was used to identify monocyte subsets (classical, intermediate and non-classical) by staff blinded to the individuals' characteristics. Variables were compared using Mann-Whitney U test and Chi-squared test, as appropriate. Eta coefficient was calculated to analyze the relationship between ethnicity and proportion of monocyte subsets. Eta squared values were calculated to assess the impact of ethnicity on monocyte subset proportions. Results: The SA group consisted of 64% males with a mean age of 54 (± 9), while the WC group consisted of 55% males with a mean age of 59 (± 7). Both groups had similar body mass index, rates of hypertension, dyslipidemia and family history of premature CAD. Compared to WC, SA had higher prevalence of diabetes (36% vs. 13%, p=0.005) and hemoglobin A1C levels (6.0±1.1% vs. 5.6±0.6%, p<0.001). SA patients had a higher proportion (85.3±10.7% vs. 81.4±11.0%, p=0.009) and total level (449.0±180.4 vs. 388±127.4, p=0.010) of classical CD14++CD16- monocytes compared to WC. There was no difference between the two groups in the proportion of intermediate CD14++CD16+ and non-classical CD14+CD16++ monocytes. There was no association between diabetes and the proportion of monocyte subsets. Ethnicity had a moderate association with the proportion of classical CD14++CD16- monocytes (Eta coefficient = 0.525) with a large effect size (Eta squared = 27.5%). The association of ethnicity with intermediate CD14++CD16+ and non-classical CD14+CD16++ monocytes was either weak or negligible with minimal to no effect size. Conclusion: In patients with substantive risk for CAD, SA had a significantly higher proportion and level of classical CD14++CD16- monocytes compared to WC. Our findings provide a novel insight into the potential mechanism of increased CAD susceptibility amongst SA compared to WC. Future studies are needed to determine whether these ethnic differences in the distribution of monocyte subsets can predict susceptibility to developing CAD and suffering atherothrombotic events. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Cardiology Academic Practice Plan grant at the University of British Columbia